OsMAPK6, a mitogen‐activated protein kinase, influences rice grain size and biomass production. (November 2015) - Liu, Shuying; Hua, Lei; Dong, Sujun; Chen, Hongqi; Zhu, Xudong; Jiang, Jun'e; Zhang, Fang; Li, Yunhai; Fang, Xiaohua; Chen, Fan
Summary: Grain size is an important agronomic trait in determining grain yield. However, the molecular mechanisms that determine the final grain size are not well understood. Here, we report the functional analysis of a rice ( Oryza sativa L.) mutant, dwarf and small grain1 ( dsg1 ), which displays pleiotropic phenotypes, including small grains, dwarfism and erect leaves. Cytological observations revealed that the small grain and dwarfism of dsg1 were mainly caused by the inhibition of cell proliferation. Map‐based cloning revealed that DSG1 encoded a mitogen‐activated protein kinase (MAPK), OsMAPK6. OsMAPK6 was mainly located in the nucleus and cytoplasm, and was ubiquitously distributed in various organs, predominately in spikelets and spikelet hulls, consistent with its role in grain size and biomass production. As a functional kinase, OsMAPK6 interacts strongly with OsMKK4, indicating that OsMKK4 is likely to be the upstream MAPK kinase of OsMAPK6 in rice. In addition, hormone sensitivity tests indicated that the dsg1 mutant was less sensitive to brassinosteroids (BRs). The endogenous BR levels were reduced in dsg1, and the expression of several BR signaling pathway genes and feedback‐inhibited genes was altered in the dsg1 mutant, with or without exogenous BRs, indicating that OsMAPK6 may contribute to influence BR homeostasis and signaling. Thus, OsMAPK6, a MAPK, plays a pivotal role in grain size in rice, via cell proliferation, and BR signaling and homeostasis. Significance Statement: Grain size is an important agronomic trait in determining grain yield, but how it is controlled is not fully understood. Here we show that the rice protein kinase MAPK6 helps regulates grain size by influencing cell proliferation and brassinosteroid responses.